THE EFFECT OF EMOTIONAL ATTACHMENT AND FANATICISM TOWARDS REPURCHASE INTENTION OFFICIAL LIGHTSTICK “CARATBONG” 3rd VERSION: (Study on K-Pop Fans SEVENTEEN in Indonesia) - Andini, Pitaloka; Widyastuti (Jurnal Ilmu Manajemen, 2024)
This research attempts to identify the effect of emotional attachment and fanaticism on repurchase intention. The independent variables of this research are emotional attachment and fanaticism. Meanwhile, the dependent variable is repurchase intention. The population of this research is K-Pop group SEVENTEEN’s fandom (CARAT) in Indonesia. The sample was adjusted to a market testing study, consists of 200 respondents. Using multiple linear regression, this research finds that emotional attachment doesn’t affect repurchase intention of the official lighstick CARATBONG. This means that even if emotional attachment is high, it does not necessarily increase repurchase intention of the Official Lightstick CARATBONG product. On the other hand, fanaticism has a positive and significant effect on repurchase intention. This means that if the level of fanaticism is high, the intention to repurchase the Official Lightstick CARATBONG product will increase. The practical implication of this research is business owner must review every design and characteristic of the products they will market, especially those related to fangirling activities.